A Temporal Analysis of Intraday Volatility of Nifty Futures on the National Stock Exchange - Ritvik Singh; Rachna Gangwar (ZBW – Leibniz Information Centre for Economics, 2018)
This paper aims to establish trends in intraday volatility in context of the Indian stock market and analyze the impact of development in the Indian economy on its stock market volatility. One minute tick data of Nifty 50 futures from Jan 1, 2011 to Aug 31, 2018 was used for the purpose of this research. Volatility was computed for each day of week and various time intervals. Our analysis shows evidence of the expected U-shaped pattern of intraday volatility (higher at the beginning and end of the day). We also observed a decline in the hourly volatility over the time period studied. However, sufficient evidence to determine the impact of development in the Indian economy on volatility in the stock market was not found.
Keywords: G10; G13; G15; 330; Risk Analysis; Intraday Volatility; National Stock Exchange of India; Nifty Futures; Temporal Analysis